CUSTOMER SATISFACTION ON MARITIME TERMINAL: CASE STUDY ON FERRY TERMINAL FACILITIES AT LUMUT, PERAK - Aizat Khairi; Syazana Hashim (Marine Frontier, 2020)
According to the development of the transport industry, the concept of quality has become apparent. This study analyses the quality of ferry terminal towards passenger satisfaction. By using survey questionnaires, data from the passengers using Lumut ferry terminal has been collected and analysed. The questionnaire collected passengers’ demographics information, services information, facilities and expectations from the service provider. The questionnaire collected demographic information, information regarding services, facilities and expectations from the service provider for the passengers. This study was aimed at providing a valuable insight into the passenger satisfaction of an organization that operates the Lumut terminal. A total of 68 questionnaires were collected, and the results were analyzed using the Social Science Statistical Package (SPSS) to examine the current passenger satisfaction status and to determine the relationship between terminal facilities and passenger satisfaction. A strong relationship between the terminal facilities and customer satisfaction was found as a result.